Association Between Benign Ovarian Tumors and Ovarian Cancer Risk: A Meta-Analysis of Ten Epidemiological Studies - Guo, Jiao; Feng, Haoshen; Gu, Xi (Frontiers in Oncology, 2022)
Background Since epidemiological evidence on the relationship between benign ovarian tumors and ovarian cancer risk has been controversial, we aimed at conducting a systematic review and meta-analysis to evaluate the association. Methods PubMed and Embase database up to April 30, 2020 were searched for eligible studies. Study-specific risk estimates were pooled using a random effects model. Results Ten articles (two cohorts, seven case-control studies, and one pooled analysis of eight case-control studies) with 10331 ovarian cancer patients were included in the study. Benign ovarian tumors were associated with an increased risk of ovarian cancer (pooled relative risk [RR]=1.39, 95% confidence interval [CI]: 1.01-1.90), with high heterogeneity among studies. The pooled RR was 2.02 (95%CI: 1.32-3.11) for two cohort studies, which was higher than the pooled result of eight case-control studies (pooled RR: 1.15; 95%CI: 0.92, 1.44). When stratifying by histological types, the pooled RRs were 1.53 (95% CI: 0.37, 6.29) and 3.62 (95%CI: 0.81, 16.20) for serous and mucinous tumor, respectively. The pooled RRs were 1.61 (95%CI: 0.65, 3.95) and 1.54 (95%CI: 1.29, 1.84) for the associations of ovarian cyst with invasive and borderline cancers, respectively. Conclusions Benign ovarian tumors maybe associated with an increased risk of ovarian cancer. Since high heterogeneity among the studies and risk of bias may exist, more studies are warranted to confirm the findings.